Implementing sustainable forest management in Asia and the Pacific : proceedings of a regional expert consultation held in Bangkok from December 12-15, 1995 - Johnson, Anne; Durst, Patrick B; Food and Agriculture Organization of the United Nations; Regional Expert Consultation on the Implementation of Sustainable Forest Management (1995 : Bangkok, Thailand) (Bangkok : Food and Agriculture Organization of the United Nations, 1997)
Proceedings of the Regional Expert Consultation on the Implementation of Sustainable Forest Management
Keywords: Sustainable forestry -- Asia -- Congresses; Sustainable forestry -- Pacific Area -- Congresses; Forest management -- Asia -- Congresses; Forest management -- Pacific Area -- Congresses